Adverse events of metronidazole and amoxicillin: Retrospective analysis of a large data set of five randomized clinical trials. (5th August 2022) - Retamal‐Valdes, Belen; Tavares, Ana Paula Laranjeira; Monique, Sarah; Pereira da Silva, Hélio Doyle; Mestnik, Maria Josefa; Duarte, Poliana Mendes; Miranda, Tamires S.; Borges, Ivan; Soares, Geisla Mary Silva; Faveri, Marcelo; Castro dos Santos, Nidia; Graças, Yasmin Teixeira das; et al.
Abstract: Aim: To evaluate the frequency of side effects associated with intake of metronidazole (MTZ) + amoxicillin (AMX) in periodontal treatment, and to explore associations between these events and patients' features. Materials and Methods: Data of five randomized clinical trials testing MTZ + AMX adjunctive to mechanical therapy were evaluated. Volunteers answered an adverse event questionnaire. Results: Information from 656 subjects was assessed. The frequency of side effects in the antibiotic‐ and placebo‐treated groups ranged from 1.0% to 17.7% and 0.9% to 13.7%, respectively. The events more frequently observed in the antibiotic than in the placebo group were diarrhoea and metallic taste ( p  < .05). Diabetes significantly raised the odds of a patient reporting discomfort (odds ratio [OR] = 2.6), diarrhoea (OR = 4.0), weakness (OR = 6.0) and excessive sleepiness (OR = 2.9). In systemically healthy volunteers, using antibiotics 3 months post‐mechanical treatment (healing phase) (OR = 3.0), being a woman (OR = 3.9) and aged ≤49 (OR = 4.5) significantly increased the chances of reporting adverse events. Conclusions: The occurrence of side effects during MTZ + AMX treatment ranged from uncommon (1%) to very common (17.7%). The main factors raising the chances of a patient reporting adverse events were diabetes and taking antibiotics in the healing phase, instead of in the active phase of treatment. Patients ≤ 49 years old and females also tend to report more side effects.